Soviet Prisoners of War in Finland and Finnish Prisoners of War in the Soviet Union During the Soviet-Finnish War of 1941–1944. - Kujala, Antti (Institute of National Remembrance Review, 2023)
The mortality among the Soviet prisoners of war in Finland and the Finnish POWs in the Soviet Union during the Soviet-Finnish War of 1941–1944 was equally high. One third of the prisoners perished on both sides of the front. Thanks to the studies carried out recently in Finland, the situation of the Russian POWs and civilian detainees is fairly well known. Some Russian historians and official quarters have, however, begun politicizing the subject. It will hardly contribute to improving our knowledge and assessment of the Soviet-Finnish war of 1941–1944.